2014
DOI: 10.1186/1471-2458-14-58
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional survey of human-bat interaction in Australia: public health implications

Abstract: BackgroundFlying foxes (megachiroptera) and insectivorous microbats (microchiroptera) are the known reservoirs for a range of recently emerged, highly pathogenic viruses. In Australia there is public health concern relating to bats’ role as reservoirs of Australian Bat Lyssavirus (ABLV), which has clinical features identical to classical rabies. Three deaths from ABLV have occurred in Australia. A survey was conducted to determine the frequency of bat exposures amongst adults in Australia’s most populous state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…Recent surveys of community members in Queensland [19] and New South Wales [20] shed light on perception of bat risk and intention to handle bats from the general population. In 2014 Young et al [19] reported a survey of residents in South East Queensland and found that 20% (140/700) of participants considered bats as a high risk to human health, 31% considered a moderate risk, and 42% considered a low risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent surveys of community members in Queensland [19] and New South Wales [20] shed light on perception of bat risk and intention to handle bats from the general population. In 2014 Young et al [19] reported a survey of residents in South East Queensland and found that 20% (140/700) of participants considered bats as a high risk to human health, 31% considered a moderate risk, and 42% considered a low risk.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25–30% of participants from the survey indicated they would handle a bat trapped in wire mesh fencing or a net over a fruit tree, and 56% would handle a bat coming into their houses. Similarly, a population-based survey in New South Wales [20] reported that a quarter of respondents would handle an injured or trapped bat. Key reasons for people reporting a willingness to handle bats included [19]: 1) protection of their families, pets, and themselves from bats, in situations such as a dead bat in the yard or a live bat in the house; 2) protection of injured or trapped bats; and 3) perception of minimal or no risk from injury if implements, gloves, or towels were used to handle bats.…”
Section: Discussionmentioning
confidence: 99%
“…When in contact with flying foxes, almost ofthe people in the study area seldom use PPE (personal protective equipment) such as leather gloves, masks, and caps due to lack of awareness. It is because they are sure that bats that enter their residencial area were in good health and not likely to transmit infectious diseases to them.The persons never thought that flying foxes could be the carriers of zoonotic diseases.A survey of adults in New South Wales showed that 15.5% of 821 respondents had held bats, even though 42% of respondents have seen or heard warnings about holding bats (Paterson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…21 A comprehensive, ongoing health promotion campaign would help ensure that key messages continue to be publicised: that bat handlers should wear personal protective equipment and be vaccinated against ABLV; all other people should avoid handling bats; and anyone scratched or bitten by a bat should receive post-exposure prophylaxis. McCall et al concluded that public health prevention efforts should focus on the risk to humans when untrained, unvaccinated people attempt to handle bats, rather than simply conveying information about ABLV.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recent studies have attempted to control for individual propensity for risk-taking and to investigate the relationship between the amount of alcohol ingested in an ED versus a non-ED drinking session. 21 There is considerable controversy over these observed associations and the role of ED-industry funding for associated research.…”
Section: The Hazardmentioning
confidence: 99%